2010
DOI: 10.1016/j.febslet.2010.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the interaction of colicin A with its co‐receptor TolA

Abstract: Edited by Stuart Ferguson Keywords:Intrinsically disordered protein Colicin A TolA NMR Protein-protein interaction a b s t r a c t Colicin A enters Escherichia coli cells through interaction with endogenous TolA and TolB proteins. In vitro, binding of the colicin A translocation domain to TolA leads to unfolding of TolA. Through NMR studies of the colicin A translocation domain and polypeptides representing the individual TolA and TolB binding epitopes of colicin A we question if the unfolding of TolA induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…S6) and the fact that different patterns of methylation were observed in both free and complexed TolAIII. Although differences do exist between the structures of TolAIII determined by x-ray (herein) and NMR methods (25), they are small, and the residues predicted to be important in the interaction of TolAIII with TA 53–107 by NMR (27) are identical to those residues shown to be involved in the x-ray structure of the TA 53–107 -TolAIII complex (Fig. 2).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…S6) and the fact that different patterns of methylation were observed in both free and complexed TolAIII. Although differences do exist between the structures of TolAIII determined by x-ray (herein) and NMR methods (25), they are small, and the residues predicted to be important in the interaction of TolAIII with TA 53–107 by NMR (27) are identical to those residues shown to be involved in the x-ray structure of the TA 53–107 -TolAIII complex (Fig. 2).…”
Section: Discussionmentioning
confidence: 94%
“…However, we have preliminary NMR data showing that the chemical shifts of a mixture of the TA 1–52 and TA 53–107 peptides were slightly different for some residues of TA 53–107 when compared with those of TA 53–107 on its own 7 . NMR data have shown that a truncated polypeptide expressing both the TolA binding region and the TolB box of ColA causes an unfolding of TolAIII in vitro , which is not apparent when the TolA binding region and TolB boxes are physically separated and added to TolAIII concurrently (27). If TolA binds TolB and ColA at different binding interfaces in the TA 1–107 -TolA-TolB trimeric complex, then it is possible that an unoccupied TolB box of ColA could interfere and cause localized unfolding of TolAIII in the TA 1–107 -TolAIII complex as unfolding of TolAIII is not observed on binding of the translocation domain of ColN, which does not possess a TolB box (27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations